Spiritualitas Politik dalam Perspektif Kristiani - Bernardus Ario Tejo Sugiarto (Jurnal Iman dan Spiritualitas, 2021)
Political Spirituality presented by Paulinus Yan Olla provides guidelines for the ideal relationship between the Catholic Church and political life, how to exercise political power inspired by the values of faith and humanity to achieve the common good. Political involvement is one way to the sanctity of life.